Family‐based risk factors for non‐suicidal self‐injury: Considering influences of maltreatment, adverse family‐life experiences, and parent–child relational risk. (14th April 2016) - Martin, Jodi; Bureau, Jean‐François; Yurkowski, Kim; Fournier, Tania Renaud; Lafontaine, Marie‐France; Cloutier, Paula
ABSTRACT: The current investigation addressed the potential for unique influences of perceived childhood maltreatment, adverse family‐life events, and parent‐child relational trauma on the lifetime occurrence and addictive features of non‐suicidal self‐injury (NSSI). Participants included 957 undergraduate students (747 females; M  = 20.14 years, SD  = 3.88) who completed online questionnaires regarding the key variables under study. Although self‐injuring youth reported more experiences with each family‐based risk factor, different patterns of association were found when lifetime engagement in NSSI or its addictive features were under study. Perceived parent‐child relational trauma was uniquely linked with NSSI behavior after accounting for perceived childhood maltreatment; adverse family‐life events had an additional unique association. In contrast, perceived paternal maltreatment was uniquely related with NSSI's addictive features. Findings underline the importance of studying inter‐related family‐based risk factors of NSSI simultaneously for a comprehensive understanding of familial correlates of NSSI behavior and its underlying features.